Aspects of the Fourth Plan Plan in Outline - Planning Commission (Planning Commission, 1969)
The Fourth Five Year Plan (Draft, 1969), prepared by the Planning Commission of India, outlines a comprehensive strategy for accelerating economic growth through balanced public and private investment. With a total proposed outlay of Rs. 24,398 crores, the plan emphasizes the creation of productive assets across key sectors such as agriculture, power, transport, housing, education, and health. It introduces a more objective and flexible approach to central assistance for states and proposes a selective continuation of centrally sponsored schemes of national importance. Targeting an annual growth rate of 5.5 percent, increased domestic savings, and self-sufficiency in foodgrains, the plan seeks to reduce poverty, address regional disparities, and strengthen India’s economic resilience and social infrastructure.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Fourth Five Year Plan; Planning Commission of India; Public Sector Outlay; Private Sector Investment; Agricultural Development; Infrastructure Development; Education and Health; Centrally Sponsored Schemes; Economic Growth Projections; Self Reliance